Jewish customs of kabbalistic origin : their history and practice - Faierstein, Morris M. (Boston : Academic Studies Press, 2013)
Jewish religious practice has been transformed by the Kabbalists of Safed in the 16th century. They brought new meaning and importance to many Biblical and rabbinic commandments and created new rituals that have become central practices for Jews of all denominations. This volume describes the origins of these traditions and explains the mystical meaning of these specific practices and rituals.
""Front ""; ""TABLE OF CONTENTS""; ""PREFACE""; ""ACKNOWLEDGMENTS""; ""INTRODUCTION""; ""THE SYNAGOGUE""; ""TALIT AND TEFILLIN ""; ""PRAYERS AND BLESSINGS""; ""SABBATH CUSTOMS""; ""MINOR OBSERVANCES""; ""APPENDIX""; ""GLOSSARY""; ""BIBLIOGRAPHY""; ""INDEX OF CITATIONS""
Includes bibliographical references (pages 120-125) and index.
Description based on print version record.
Keywords: Judaism -- Customs and practices -- History; Fasts and feasts -- Judaism; Cabala -- Influence; RELIGION / Judaism / General; Cabala -- Influence; Fasts and feasts -- Judaism; Judaism -- Customs and practices; Cabala - Influence; Electronic books; History; Electronic books